(untitled) (Research, Society and Development, 2022)
Objective: To analyze in the scientific literature the care provided by nurses for the prevention of pressure injuries in patients in the Intensive Care Unit. Method: This is an integrative literature review, carried out through the databases of the VHL, LILACS, SCIELO and BDENF, with the Descriptors: "Nursing Care", "Pressure Injury" and "Intensive Care Unit", combined with each other by the Boolean operator AND. 292 studies were found and 12 studies were selected to compose the review. Results: The hospitalization of the patient in the intensive care unit causes multifactorial problems, including pressure injuries. The high incidence of this pathology is due to the severity of the disease, hospitalization and lack of adequate preparation of the team responsible for patient care in the ICU. Conclusion: From this perspective, it is clear that all preventive measures need improvements for quality nursing care for the prevention of pressure injuries, since patients admitted to the ICU in the long term develop the injury. It is important to implement prevention protocols based on the identification and management of risks and training with the nursing team to reduce cases.